The Perception of Financial Statement Users in Indonesia Towards Internet Financial Reporting (IFR) - Ispon Asep Yurano; Siti Nurwahyuningsih Harahap (The Indonesian Journal of Accounting Research, 2015)
Abstract: This study seeks to explore the perception of financial statement users regarding Internet Financial Reporting (IFR) practices in Indonesia. Based on 200 questionnaires distributed to financial statement users that are familiar with the internet, only 156 questionnaires that can be further analyzed using Kruskal-Wallis and Mann-Whitney test. The result showed that financial statement users in Indonesia found that the financial information provided on the company website is quite accurate, relevant, and relatively easy to obtain, but the information provided was difficult to be processed. As for financial information in external party website, financial statement users assess that external party website more readily available than the financial information contained in the company' website. Also, financial statement users also perceive that the usefulness of IFR still lacks, especially on the adequacy of information, so that financial statement users are still relying on other sources of information for decision making. As for ease of use IFR, financial statement users have different perceptions, in which the perceptions of differences caused by differences in the characteristics of respondents regarding work experience, education level, educational background, and frequency of use of the internet to search for financial information. Abstrak: Penelitian ini berusaha untuk mengeksplorasi persepsi pengguna laporan keuangan mengenai praktik Pelaporan Keuangan Internet (IFR) di Indonesia. Berdasarkan 200 kuesioner yang didistribusikan ke pengguna laporan keuangan yang akrab dengan internet, hanya 156 kuesioner yang dapat dianalisis lebih lanjut menggunakan Kruskal-Wallis dan tes Mann-Whitney. Hasil penelitian menunjukkan bahwa pengguna laporan keuangan di Indonesia menemukan bahwa informasi keuangan yang disediakan di situs web perusahaan cukup akurat, relevan, dan relatif mudah diperoleh, tetapi informasi yang diberikan sulit untuk diproses. Adapun informasi keuangan di situs web pihak eksternal, pengguna laporan keuangan menilai bahwa situs web pihak eksternal lebih mudah tersedia daripada informasi keuangan yang terdapat di situs web perusahaan. Selain itu, pengguna laporan keuangan juga merasakan bahwa kegunaan IFR masih kurang, terutama pada kecukupan informasi, sehingga pengguna laporan keuangan masih mengandalkan sumber informasi lain untuk pengambilan keputusan. Adapun kemudahan penggunaan IFR, pengguna laporan keuangan memiliki persepsi yang berbeda, di mana persepsi perbedaan disebabkan oleh perbedaan karakteristik responden mengenai pengalaman kerja, tingkat pendidikan, latar belakang pendidikan, dan frekuensi penggunaan internet untuk mencari informasi keuangan.